Linear, mixed-valent homocatenated tri-tin complexes featuring Sn–Sn bonds. Issue 50 (19th May 2020) - Chang, Wei-Chieh; Raj, Ankit; Hiramatsu, Hirotsugu; Li, Han-Jung; Ziegler, Micah S.; Lin, Yichen; Huang, Shengcih; Liu, Hsueh-Ju
Abstract : Reduction of L Ph SnCl with 0.66 eq. of LiB s Bu3 H affords the mixed-valent homocatenated tri-tin complex (L Ph Sn)3 Cl whose HOMO primarily comprises σ-bonding along the Sn–Sn–Sn framework. Abstract : A series of tri-tin complexes (L Ph Sn)3 X with triple-decker structures (L Ph = 2, 5-di( o -pyridyl)-3, 4-diphenylpyrrolate; X = Cl, AlCl4, OTf, and PF6 ) was synthesized by reducing L Ph SnCl with LiB s Bu3 H and subsequent reactions. Structural characterization of (L Ph Sn)3 Cl revealed a Sn–Sn–Sn core, and DFT calculations suggest that its HOMO is primarily σ-bonding along the tri-tin framework. (L Ph Sn)3 Cl reacts with W(CO)5 THF to afford (L Ph Sn)2 (W(CO)5 )2 and L Ph SnCl, implying that (L Ph Sn)3 Cl may exhibit dynamic behavior in solution.